2021
DOI: 10.1084/jem.20191314
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ is essential for the development of bone marrow erythroblastic island macrophages and splenic red pulp macrophages

Abstract: Tissue-resident macrophages play a crucial role in maintaining homeostasis. Macrophage progenitors migrate to tissues perinatally, where environmental cues shape their identity and unique functions. Here, we show that the absence of PPARγ affects neonatal development and VCAM-1 expression of splenic iron-recycling red pulp macrophages (RPMs) and bone marrow erythroblastic island macrophages (EIMs). Transcriptome analysis of the few remaining Pparg-deficient RPM-like and EIM-like cells suggests that PPARγ is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 62 publications
(100 reference statements)
10
35
0
Order By: Relevance
“…We focussed on EGR2, which is part of a family of early growth response (EGR) transcription factors, comprising EGR1-4, as Egr2 appeared to be expressed in a particularly selective manner by alveolar macrophages ( Figure 1D ) when compared with other tissue macrophages at mRNA ( Figure 1E ) and protein level ( Figure 1F, G & Supplementary Figure 2A ). In contrast, while highly expressed by alveolar macrophages, Pparg was also expressed at a high level by splenic red pulp macrophages ( Figure 1E ), consistent with previous reports (12, 13) . Next, we performed analogous analysis of EGR2 expression across a variety of human macrophage populations from scRNA-seq data sets within the Human Cell Atlas.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…We focussed on EGR2, which is part of a family of early growth response (EGR) transcription factors, comprising EGR1-4, as Egr2 appeared to be expressed in a particularly selective manner by alveolar macrophages ( Figure 1D ) when compared with other tissue macrophages at mRNA ( Figure 1E ) and protein level ( Figure 1F, G & Supplementary Figure 2A ). In contrast, while highly expressed by alveolar macrophages, Pparg was also expressed at a high level by splenic red pulp macrophages ( Figure 1E ), consistent with previous reports (12, 13) . Next, we performed analogous analysis of EGR2 expression across a variety of human macrophage populations from scRNA-seq data sets within the Human Cell Atlas.…”
Section: Resultssupporting
confidence: 92%
“…We did not detect differences in the proliferative activity of Egr2- sufficient and - deficient alveolar macrophages ( Figure 2G ). Importantly and consistent with the lack of EGR2 expression by other tissue resident macrophages, we saw no effect on the cell number and expression of signature markers by resident macrophages in other tissues, including in the spleen where macrophages share a dependence on PPAR-γ (12, 13) ( Supplementary Figure 3B, C ). Thus, these data demonstrate that while EGR2 expression is dispensable for alveolar macrophages survival and self-maintenance, it is indispensable for imprinting key phenotypic features of the cells in the healthy lung.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…RPM express high levels of α9 integrin, a known ligand of various extracellular matrix proteins such as fibronectin and tenascin‐C, which are abundant in the spleen 62,139‐141 . Transcriptional analyses revealed that developing RPM upregulate αD integrin, possibly contributing to their retention within the RP 142 . As introduced, RPM also express Spi C, which potently induces VCAM‐1 in these macrophages 51 .…”
Section: The Concept Of the Macrophage Nichementioning
confidence: 99%